2011
DOI: 10.1002/ejic.201100423
|View full text |Cite
|
Sign up to set email alerts
|

Dicarbonylrhodium(I) Complexes of Bipyridine Ligands with Proximate H‐Bonding Substituents and Their Application in Methyl Acetate Carbonylation

Abstract: A series of cationic cis-dicarbonylrhodium(I) complexes [Rh(L)(CO) 2 ]SbF 6 has been prepared containing 2,2Ј-bipyridine ligands with proximate H-bonding substituents R in the 6-and 6Ј-position (R = OH, NH 2 , COOEt and PO(OEt) 2 ). The solid-state structures have been determined by X-ray crystallography for the complexes where R = OH, NH 2 and COOEt. The molecular structures have revealed metal-metal and π-π interactions between the square-planar complexes resulting in the formation of molecular chains in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Crystals of 1·[Rh(CO) 2 ][Rh(CO) 2 Cl 2 ]w ere exposed to CH 3 Br vapor in dry acetonitrile (CH 3 CN) for 11 days,a nd then washed with fresh CH 3 CN ( 6) prior to examination by SCXRD.A nalysis of the X-ray data confirmed that 1·[Rh-(CO) 2 ][Rh(CO) 2 Cl 2 ]h ad transformed to an octahedral Rh III species, 1·[Rh(CH 3 CN) 2 (COMe)Br]Br ( Figure 1);t he presence of aB r À in the structure suggests that the Rh I anion of the starting material had also reacted with MeBr and was expelled from the MOF.T he product formulation was supported by IR spectroscopy,which shows stretches characteristic of coordinated CH 3 CN molecules [16] at 2320 and 2300 cm À1 and aRh-bound acetyl group [17] at 1726 cm À1 in the spectra of 1·[Rh(CH 3 CN) 2 (COMe)Br]Br (see Figure 3). Furthermore,n op eaks are observed between 1990 and 2100 cm À1 ,s upporting the reaction of the carbonyl ligands.…”
mentioning
confidence: 98%
“…Crystals of 1·[Rh(CO) 2 ][Rh(CO) 2 Cl 2 ]w ere exposed to CH 3 Br vapor in dry acetonitrile (CH 3 CN) for 11 days,a nd then washed with fresh CH 3 CN ( 6) prior to examination by SCXRD.A nalysis of the X-ray data confirmed that 1·[Rh-(CO) 2 ][Rh(CO) 2 Cl 2 ]h ad transformed to an octahedral Rh III species, 1·[Rh(CH 3 CN) 2 (COMe)Br]Br ( Figure 1);t he presence of aB r À in the structure suggests that the Rh I anion of the starting material had also reacted with MeBr and was expelled from the MOF.T he product formulation was supported by IR spectroscopy,which shows stretches characteristic of coordinated CH 3 CN molecules [16] at 2320 and 2300 cm À1 and aRh-bound acetyl group [17] at 1726 cm À1 in the spectra of 1·[Rh(CH 3 CN) 2 (COMe)Br]Br (see Figure 3). Furthermore,n op eaks are observed between 1990 and 2100 cm À1 ,s upporting the reaction of the carbonyl ligands.…”
mentioning
confidence: 98%
“…Analysis of the X-ray data confirmed that 1•[Rh(CO)2][Rh(CO)2Cl2] had transformed to an octahedral Rh(III) species, 1•[Rh(CH3CN)2(COMe)Br]Br (Figure 1); the presence of a Brin the structure suggests that the Rh(I) anion of the starting material had also reacted with MeBr and is expelled from the MOF. The product formulation was supported by IR spectroscopy, which shows stretches characteristic of coordinated CH3CN molecules [16] at 2320 and 2300 cm -1 and a Rh-bound acetyl group [17] at 1726 cm -1 in the spectra of 1•[Rh(CH3CN)2(COMe)Br]Br (Figure 3). Furthermore, no peaks were observed between 1990 and 2100 cm -1 , supporting the reaction of the carbonyl ligands.…”
mentioning
confidence: 99%
“…In 2011, Britovsek et al were the first to report a dicarbonyl Rh complex ( 9) with 6,6 0 -dihydroxy-2,2 0 -bipyridine (6DHBP). 45,46 [Rh(6DHBP)(CO) 2 ]SbF 6 was used for the carbonylation of methanol to acetic acid with CO. 46,47 However, it gave similar results (TOF: 180 h À1 ) as the unfunctionalized catalyst, [Rh(bpy)(CO) 2 ]SbF 6 (TOF: 220 h À1 ).…”
Section: Hydroxy Group At the Ortho Positionmentioning
confidence: 68%